The Intertextuality of In Dubio Pro Reo and In Dubio Pro Natura in the Occurrence of Environmental Crimes - Vincentius Patria Setyawan (CV Tirta Pustaka Press, 2026)
Despite the increasing prosecution of environmental crimes, environmental criminal law scholarship has yet to systematically address how the presumption of innocence, embodied in the maxim in dubio pro reo, operates in cases characterized by scientific uncertainty and diffuse ecological harm, creating a doctrinal gap in balancing procedural safeguards with ecological protection. While this principle safeguards the rights of the accused, its rigid application often conflicts with the need for ecological justice in environmental crime cases, where the victims are not individuals but ecosystems themselves. The emerging principle in dubio pro natura, which promotes environmental protection as a legal priority in ambiguous situations, offers a counterbalance but remains underdeveloped in doctrinal formulation, theoretical grounding, and consistent judicial application. This study argues for a context-sensitive interpretative framework that reconciles in dubio pro reo and in dubio pro natura in the adjudication of environmental crimes. Adopting a normative juridical method grounded in doctrinal legal analysis, this study examines statutory provisions, judicial decisions, and scholarly interpretations at both national and international levels. The findings identify a doctrinal inconsistency affecting evidentiary standards, burden of proof, and preventive enforcement mechanisms In several cases, the application of in dubio pro reo has undermined preventive environmental enforcement, while the potential of in dubio pro natura remains largely rhetorical. The study concludes that a balanced and context-sensitive integration of both principles is necessary to optimize justice, not only for human defendants but also for nature as a legal subject, particularly in prosecuting complex environmental crimes.